(untitled) (International Journal of Environmental Sciences, 2025)
The current study aimed to assess the effect of addition of prepared polyester in three concentrations to the polymethylmethacrylate and analyze its effect on the underlying structure in the mandibular arch. Unsaturated polyester was prepared by the condensation polymerization of maleic anhydride with di ethylene glycol and used in three concentrations (1%,3% and 5%) for addition to the polymethylmethacrylate to prepare the denture base. Four specimens were fabricated according to the international standards specifications , Rectangular specimen with specific measures (65mm length, 10mm width and 3mm thickness) was used to measure the modulus of elasticity of the modified poly methylmethacrylate in different concentration. The modulus of elasticity was obtained from Universal testing machine (INSTRON, USA). Then load-deflection curves were recorded by the connected computer software (Bluehill v1.5; Instron Ltd). From load-deflection curves, the elastic modulus was calculated according to following formula: E = FL3/4Ybd3 where E= Flexural modulus (MPa), F=maximum load (N), L=span length (65 mm), Y=recorded deflection when the load is applied at the middle of the beam, b=specimen width (10 mm), d=specimen thickness (3mm). Autodesk Inventor is a Computer-Aided Design (CAD) software developed by Autodesk.it is used to design the model which is mandibular arch for the finite element analysis in this study. The results of the finite element analysis revealed that the sample with 3% polyester showed the better stress distribution and give better results in the Von Mises stress, Equivalent Strain and Displacement values.